Educaç\~ao profissional, exigências da ocupaç\~ao e rendimentos do trabalho no Brasil - Maurício Cortez Reis; Marina Ferreira Fortes Aguas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper estimates the consequences of mismatches between workers' attainment of vocational education and requirement of this type of qualification in their occupations in Brazil. Two types of vocational education are investigated here: vocational training and secondary vocational education, which are the most important in Brazil. Combining data from the 2007 PNAD and the 2010 Brazilian Classification of Occupations, indicators of required qualification can be imputed to each employed individual according to his or her occupation. Thus, based on the attainment of vocational education, workers in the sample can be classified as adequately matched, overqualified or underqualified. Estimates indicate that the lack of required qualification seems to have negative consequences on labor earnings, and that workers with vocational education earn more than those who did not complete a course of this type even in occupations where vocational education is not need.
Keywords: J24; J31; I21; 330; vocational education and training; occupational skill requirements; labor earnings